(In)visible ink: Outsiders at the Yaji, the ink installations of Bingyi and Tao Aimin. (1st September 2018) - Guest, Luise
The yaji in Imperial China was an 'elegant gathering' of scholars who met to play chess, listen to music, and appreciate ink painting and calligraphy. They were generally all-male affairs, often taking place in a walled garden. Recently it has been argued that such forms of semi-private contemplation are appropriate models for exhibiting Chinese contemporary art. This article has two connected parts: the first examines how two women artists, Tao Aimin and Bingyi, 'outsiders' to the yaji garden gathering as it was traditionally constructed, subvert (yet also honour) important Chinese traditions. They challenge a gendered historical narrative by means of a reinvigorated and performative ink language, negotiating literal and figurative 'inside' and 'outside' spaces. Positioned as reconfiguring space in a way that challenges binaries of inside/outside, they interrogate the literati tradition that functioned as an expression of class and gender. Two works in particular exemplify their practice: Bingyi's Époché, a 2014 performance in which she dropped 500 kilograms of ink/oil 'missiles' from a helicopter over the airfield at Shenzhen Bao'an Airport, and Tao Aimin's 2008 The Secret Language of Women, an installation of bound books printed from rural women's washboards employing the ancient Nüshu script invented by rural women. The second part of the article critically examines contemporary iterations of the yaji as a model for the exhibition of contemporary art. The term yaji is thus used in two ways in this article: as a metaphor to reflect on the absence of women artists in the reinvented literati ink tradition, and in a critical examination of its real-world manifestations in several recent exhibitions. In this context, the works of Tao Aimin and Bingyi occupy a complicated liminal space: they position themselves at times inside feminist discourse and at other times disavow a connection; they occupy a marginal space within dominant contemporary art world discourses and historically masculine discourses around calligraphy and the yaji, yet 'inside' the ink tradition. This article was developed from a paper presented at the Annual Conference of the Centre for Chinese Visual Art, School of Art, Birmingham City University, 13 October 2017.